Proposed Council directives on excise duties and similar taxes (transmitted on 7 March 1972) - Commission of the European Communities (Brussels : [Distributed in U.S.A. by European Community Information Service, Washington, D.C.], 1972)
This handbook is a proposal that provides a detailed procedure to council directive on excise duties and indirect taxes, other than value added tax, which are levied directly, or indirectly on the consumption of products
Cover title: Proposals for harmonizing consumer taxes other than VAT.
Includes bibliographical references.
obn 24/01/2019
Loans
Keywords: Taxation of articles of consumption; Law; Excise tax